Public Policy, Start-up Entrepreneurship, and the Market for Venture Capital - Søren Bo Nielsen; Christian Keuschnigg (Copenhagen Business School (CBS), Department of Economics, 2006)
In recent years, venture capital has become an important source for nancing young entrepreneurial rms. Given the apparently more innovative nature and extra value added of venture capital backed rms compared to other firms, policy makers have taken an increasing interest in an active venture capital industry. We explore how selected policy instruments determine the incentives of individuals to start up new rms and of venture capitalists to nance and advise them, and how policy thereby influences the size and nature of the industry and how it aspects aggregate welfare. We examine the impact of wage and corporate income taxes as well as capital gains taxes and start-up capital subsidies on the volume and quality of venture capital backed entrepreneurship.
hdl:10398/7569
Keywords: D82; G24; H24; H25; 330; entrepreneurship; venture capital; double moral hazard; taxes; subsidies